30S Ribosomal Subunit Assembly Is a Target for Inhibition by Aminoglycosides in Escherichia coli - Mehta, Roopal (American Society for Microbiology, 2002)
The aminoglycosides paromomycin and neomycin were examined in Escherichia coli cells for an inhibitory effect on 30S ribosomal subunit assembly. Both compounds inhibited the growth rate, viable cell number, and protein synthesis rate with similar 50% inhibitory concentrations. Each drug also showed a concentration-dependent inhibition of 30S subunit formation. The inhibitory effect on 30S particle formation was approximately equivalent to the inhibitory effect on translation for these antibiotics.